Protection of Human Rights on The Life of Indigenous Communities in Bali - Anak Agung Linda Cantika; I Gede Yusa; Putu Gede Arya Sumerta Yasa; Sagung Putri M.E. Purwani (Journal of Sustainable Development Science, 2026)
This study aims to analyze the protection of human rights within the life of indigenous peoples (masyarakat hukum adat) in Bali. This issue becomes particularly significant when examined in light of the constitutional recognition under Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia, which acknowledges the existence and rights of indigenous communities. Such recognition entails not only an obligation to respect and protect these rights, but also to ensure their fulfilment. Human rights, as stipulated in Law Number 39 of 1999 on Human Rights, fundamentally represent inherent powers or entitlements possessed by individuals. Given their fundamental nature, the fulfilment of these rights is imperative. In practice, indigenous communities in Bali constitute organized social entities governed by customary law, residing within defined territories, possessing leadership structures, and holding both tangible and intangible assets, including control over natural resources within their territorial domain. This research employs an empirical legal method, conceptualizing law as a social phenomenon observable within real-life contexts. Referring to human rights enforcement, Article 6 paragraph (1) emphasizes that the needs of indigenous communities must be acknowledged and protected by law, society, and the government. Human rights protection for indigenous communities in Bali encompasses several key aspects, including: the rights of women and children; the prohibition of cruel and inhumane punishment in relation to customary sanctions; land rights associated with the protection of cultural identity and communal land rights (hak ulayat); and the rights of local communities in tourism development, considering Bali’s position as a major tourism hub.